2016
DOI: 10.1007/s11011-016-9830-1
|View full text |Cite
|
Sign up to set email alerts
|

Early and sustained exposure to high-sucrose diet triggers hippocampal ER stress in young rats

Abstract: Early-life environmental insults have been shown to promote long-term development of chronic non-communicable diseases, including metabolic disturbances and mental illnesses. As such, premature consumption of high-sugar foods has been associated to early onset of detrimental outcomes, whereas underlying mechanisms are still poorly understood. In the present study, we sought to investigate whether early and sustained exposure to high-sucrose diet promotes metabolic disturbances that ultimately might anticipate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Previous studies suggested that the hippocampus is particularly sensitive to high-fat/high-sugar diets especially when the consumption starts during developmental periods [30,[45][46][47]. Highly palatable food affects the structural and functional integrity of the hippocampus [48] and high sucrose consumption activates endoplasmic reticulum stress pathways [47] and modifies synaptic plasticity in the hippocampus [49]. Hippocampus regulates DA neurons located in the ventral tegmental area (VTA) [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the hippocampus is particularly sensitive to high-fat/high-sugar diets especially when the consumption starts during developmental periods [30,[45][46][47]. Highly palatable food affects the structural and functional integrity of the hippocampus [48] and high sucrose consumption activates endoplasmic reticulum stress pathways [47] and modifies synaptic plasticity in the hippocampus [49]. Hippocampus regulates DA neurons located in the ventral tegmental area (VTA) [50].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic effects of sucrose consumption examined together with a high fat diet might be different from those associated with a normal fat diet57. In addition, the initiating time point in the life cycle and duration of the sucrose challenge might be important contributing factors275663. Animal strain differences might also contribute to the discrepancy as well.…”
Section: Discussionmentioning
confidence: 99%
“…Basal glucose was very similar in the three groups, with values of 70.1±12.7, 72.8±8.11, and 70.±11.3 mg/dL in the C, PA, and LA groups, respectively ( Figure 1I). The triglyceride-glucose (TyG) index, a marker of insulin resistance and metabolic syndrome, [25][26][27][28] was not changed between the control (C) and androgenized groups (PA or LA). As shown in Figure 1J, there were no significant differences in TYG index values in the C group (1,362±392), PA group (1,288±244.3), and LA group (1,336±1,206.5).…”
Section: Resultsmentioning
confidence: 99%